Effect of Pre-cooling Combined with Exogenous Oxalic Acid Application on Storage Quality of Mango (Mangifera indica) - Wijewardane , R M N A (Journal of Postharvest Technology, 2014)
This study was undertaken to determine low cost treatments that  may be readily adoptable by local producers and exporters to  extend the storage life of mango. The experiment was conducted  for the var. ‘Karuthacolomban’. The fruits were harvested 13  weeks after flowering. Just after harvesting, the half of the lots  of selected fruits were subjected to pre-cooling by using hydro pre-cooling (water temperature 15ºC) till the fruit temperature  reaches to 13-15ºC and remaining was kept without pre-cooling.  The pre-cooled and non pre-cooled fruits were dipped in 5%  sodium bicarbonate solution for 10 min followed by 6 and 8  ppm oxalic acid solution for 10 min, air-dried and the treated  fruits were stored at ambient (28-30ºC, 65-70% RH) and low  temperature (13±2ºC, 55-60% RH) conditions. The fruits from  each treatment were observed to evaluate the physiological  weight loss, fruit firmness, total soluble solids, titratable acidity,  pH and rate of respiration. The results revealed that fruits dipped  in 5% sodium bicarbonate solution followed by 8 ppm oxalic  acid application along with pre-cooling was the most effective  for extension of storage life of fresh mango up to 12 and 24 days  under ambient (28-30ºC, 65-70% RH) and low temperature  storage (13±2ºC, 55-60% RH), respectively. Fruits stored under  low temperature exhibited better retention of all physiological  and biochemical characteristics than the same treatments during  ambient storage.
Keywords: Pre-cooling; Oxalic acid; Sodium bicarbonate Mango; Storage